Sustainability studies of smallholder livestock based on climatological conditions, land resources and farmer profile - Anggraini, L.J.; Panjono, Panjono; Ngadiyono, N.; Bintara, S.; Baliarti, E. (2021)
Bali Island is one of the islands in Indonesia that is vulnerable to climate change. To support mitigation and adaptation efforts, information on climate change in Bali is needed. Sustainability in the field of animal husbandry is of course very important. Especially for beef cattle,. The aim is to assess the sustainability of smallholder livestock based on climatological conditions, land resources, and farmer profiles. The research was conducted in Bangli and Gianyar Regencies, Bali Province. The material used is 200 farmers with direct interviews. The method used was the Participating Rural Appraisal (PRA) survey. The results of the research on land resources in Bangli Regency were 42,502 ha of plantation land (29.92) with the type of coffee plantation, while in Gianyar Regency using an area of 14,790 ha (40.19). From the breeder profile. The results showed that most of the farmers were old, had low education, had low main jobs as breeders and livestock. The positive thing is that farming takes a long time and has good detection capabilities so that it can be detrimental to the experience that climatological conditions, land resources, and farmer profiles can continue for small farmers in Bali. Â© Published under licence by IOP Publishing Ltd.